2015
DOI: 10.5649/jjphcs.41.630
|View full text |Cite
|
Sign up to set email alerts
|

The Cause of Contamination for Blister Pack Containing Fluorouracil Oral Tablets

Abstract: We recently reported that various amounts of cyclophosphamide (CP) had contaminated both the inside and outside of the blister pack, and refrigerated storage of CP oral tablets can protect healthcare workers and patients from contact CP exposure. However, the contamination from a non-volatile agent, fluorouracil (FU), and its preventive procedures are not elucidated. Here we showed high levels of FU were detected from inside the blister pack. Raman imaging showed that the FU ingredient was not attached to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…For oral HDs, such as cyclophosphamide or 5-fluorouracil tablets, the risk of exposure to HDs was evaluated by analysing the amount of drugs on the surfaces of the blister packages, and the amount of HDs that may be inadvertently ingested by caregivers during drug administration using feeding tubes 10–12. In a study of injectable anticancer drugs, Böhlandt et al reported that drugs were dispersed via sweat, saliva, and excrement in the homes of patients treated with anticancer drugs 13.…”
Section: Introductionmentioning
confidence: 99%
“…For oral HDs, such as cyclophosphamide or 5-fluorouracil tablets, the risk of exposure to HDs was evaluated by analysing the amount of drugs on the surfaces of the blister packages, and the amount of HDs that may be inadvertently ingested by caregivers during drug administration using feeding tubes 10–12. In a study of injectable anticancer drugs, Böhlandt et al reported that drugs were dispersed via sweat, saliva, and excrement in the homes of patients treated with anticancer drugs 13.…”
Section: Introductionmentioning
confidence: 99%